ISOLATION, IDENTIFICATION, AND MANAGEMENT OF IN VITRO PHYTOPHTHORA NICOTIANAE, THE CAUSATIVE AGENT OF CITRUS GUMMOSIS (Journal of Plant Disease Sciences, 2025)
Various Phytophthora species have long been reported to cause different citrus diseases, including gummosis, root rot, fruit brown rot, and citrus decline worldwide, including in India. Among these, Phytophthora nicotianae has gained considerable attention due to its ability to cause citrus gummosis, leading to significant yield losses (approximately 10-30%).Considering this, the present study aimed to isolate the pathogen from infected plants, identify it based on morphological and microscopic characteristics, and evaluate its management using novel in vitro fungicides. The pathogen was isolated from gummosis-infected soil samples using the leaf bait method and exhibited cottony dense mycelium and aseptate hyphae as key morphological characteristics. Fungicide tests revealed 100% inhibition of P. nicotianae at a 2500 ppm concentration under laboratory conditions.
Keywords: Phytophthora nicotianae; Isolation; Fungicide; Inhibition